Safety evaluation of aqueous extracts of Sanghuangporus vaninii fruiting body in Sprague–Dawley rats. Issue 9 (5th August 2020) - Huo, Jinxi; Sun, Yuqing; Zhong, Shi; Li, Yougui; Yang, Ruchun; Xia, Lijuan; Wang, Jiahong; Zhang, Majuan; Zhu, Jianxun
Abstract: Sanghuangporus vaninii, called "Sanghuang, " is orally used for health care, tumor, and inflammation treatment in Asia. However, the safety of S. vaninii has not been evaluated. The major compounds analysis showed that aqueous extracts of S. vaninii fruiting body were rich in polysaccharides, nucleotides, and polyphenols. Then, the aqueous was given orally to Sprague–Dawley rats for toxical test. In acute toxicity study, the maximum tolerated dose was 21 g/kg. In 17‐week repeated dose toxicity experiment, all rats had no abnormal reaction among control group, low dose group (0.15 g/kg) and middle dose group (1.00 g/kg). At high dose group (6.00 g/kg), the feces began to darken on 16th day (D16), and turned to drug stained stool on D21, all rats recovered on the 3rd day (D92) of recovery period. During the whole experiment, there were no animal death and no treatment‐related changes in any of the parameters under the all doses. These results indicated the No‐Observed Adverse Effect Level of aqueous extract of S. vaninii fruiting body was 1.0 g/kg. Abstract : The LD 0 and NOAEL of aqueous extracts of Sanghuangporus vaninii fruiting body were 21 and 1.0 g/kg, respectively. These data suggested S. vaninii could be considered as nonpathogenic and safe for human consumption as a traditional Chinese medicine for daily health preservation.